POLITIK MULTIKULTURAL ETNIS TIONGHOA PASCA-REFORMASI DI KOTA MEDAN - Deny Setiawan (Millah: Journal of Religious Studies, 2013)
This research proposed to get a factual description about multicultural politics of Chinese at post-reform in Medan. Factuality multicultural politics explored through the perspective of Chinese leaders thinking about the themes reconceptualization of integration and reconstruction of national identity. Empirical data of the two themes, used as input in the development of a multicultural society project in Medan. Collection of data was performed by assessment techniques documentation, observation and interviews. Data analysis using analytic comparison that in the data processing included in the method of agreement and method of difference. The research findings indicate (1) the perspective thinking of the Chinese leaders in reconceptualization of integration leads to the choice of "integrated-pluralism" as a polity that is considered more appropriate in establishing the post-reform integration in Medan, (2) ideas, demands and expectations of the Chinese leaders about the reconstruction of national identity formulations produce a national identity that is more fitting for Indonesia in the era of globalization, the "hybrid identity”. This formulation describes the Indonesian identity continues to be fluid and dynamic, and (3) the synergy of these two themes show has been a shift from cultural pluralism to multiculturalism that in the arrangement still requires time and a more conducive atmosphere.